Implementation of environmental education strategies and their contribution to college students' commitment to biodiversity conservation - Ardan, Andam Surianty (Jurnal Konseling dan Pendidikan, 2025)
This study explores the implementation of environmental education strategies and their contribution to college students' commitment to biodiversity conservation. Using a qualitative approach through a literature review, the study aims to understand how environmental education can influence students' environmental awareness and behavior. The literature highlights the importance of integrating biodiversity conservation topics into college curricula, emphasizing hands-on learning, fieldwork, and collaborative projects. These strategies promote greater student engagement and foster a deeper understanding of ecological systems and conservation efforts. The findings reveal that environmental education enhances students' knowledge and positively influences their attitudes toward biodiversity, leading to stronger personal commitments to conservation. Moreover, it highlights the role of interactive learning environments in encouraging students to become active participants in sustainability initiatives. The study also identifies barriers, such as lack of resources and insufficient faculty training, which may hinder the effective implementation of these strategies. Recommendations for future research and practice include expanding environmental education programs, training educators in conservation topics, and creating more opportunities for student involvement in real-world biodiversity projects. By addressing these challenges, environmental education can play a pivotal role in empowering college students to contribute meaningfully to biodiversity conservation efforts. The findings underscore the need for a continuous and adaptive approach to environmental education that reflects the dynamic challenges of biodiversity conservation in a global context.